Association between the "Timed Up and Go Test" at transplant evaluation and outcomes after kidney transplantation. Issue 11 (28th October 2018) - Michelson, Ariane T.; Tsapepas, Demetra S.; Husain, S. Ali; Brennan, Corey; Chiles, Mariana C.; Runge, Brian; Lione, Jennifer; Kil, Byum H.; Cohen, David J.; Ratner, Lloyd E.; Mohan, Sumit
Abstract: Background: Studies have demonstrated the Timed Up and Go Test's (TUGT) ability to forecast postoperative outcomes for several surgical specialties. Evaluations of the TUGT for waitlist and posttransplant outcomes have yet to be examined in kidney transplantation. Objective: To assess the prognostic utility of the TUGT and its associations with waitlist and posttransplant outcomes for kidney transplant candidates. Design and Methods: Single‐center, prospective study of 518 patients who performed TUGT during their transplant evaluation between 9/1/2013‐11/30/2014. TUGT times were evaluated as a continuous variable or 3‐level discrete categorical variable with TUGT times categorized as long (>9 seconds), average (8‐9 seconds), or short (5‐8 seconds). Results: Transplanted individuals had shorter TUGT times than those who remained on the waitlist (8.99 vs 9.79 seconds, P  < 0.001). Bivariable and multivariable logistic regression showed that after adjusting for age, there was no association between TUGT times and probability of waitlist removal (OR 0.997 [0.814‐1.221]), prolonged length of stay posttransplant (OR 1.113 [0.958‐1.306] for deceased donor, OR 0.983 [0.757‐1.277] for living donor), and 30‐day readmissions (OR 0.984 [0.845‐1.146] for deceased donor, OR 1.254 [0.976‐1.613] for living donor). Conclusions: The TUGT was not associated with waitlist removal or prolonged hospitalization for kidney transplant candidates. Alternative assessments of global health, such as functional status or frailty, should be considered for evaluation of potential kidney transplant candidates.